REVOLUSI PROMOSI PERPUSTAKAAN DI ERA DIGITAL: INOVASI STRATEGIS MELALUI MEDIA SOSIAL DI LINGKUNGAN PERGURUAN TINGGI - Rahmi, Lailatur; Tridola, Regita; Rahmayuni, Suci (UIN Imam Bonjol Padang, 2025)
Digital technology advancement has transformed the library promotion paradigm, particularly within higher education institutions. This article explores innovative strategies in library promotion through the use of social media as a communication and institutional branding tool, based on research conducted at the UIN Imam Bonjol Padang Library. Employing a descriptive method with a qualitative approach, the study includes observation, interviews, and documentation analysis. The findings reveal that platforms such as Instagram, Facebook, and WhatsApp have been actively utilized to disseminate information on library services, activities, and collections. Social media-based promotion proves to be effective in reaching digital-native students and enhancing user engagement and institutional image. However, challenges such as limited human resources and lack of structured content planning remain. This article highlights the importance of integrated and sustainable promotional strategies to support the digital transformation of academic libraries in the information revolution era.